The diverse role of the Urological Surgical Care Practitioner: A brief examination. Issue 3 (9th September 2019) - Fletcher, Nicholas; Russell, Bradley
ABSTRACT: Aim: To understand the different roles and aspects of the Surgical Care Practitioner (SCP) in delivering urology care to patients. To identify the different activities and various settings that SCP's are active in. Method: Data collection was via online survey, distributed to 12 Urology SCP's from around the United Kingdom. Results: 83% response rate was recorded. The Majority of SCP's time is spent in the Operating Theatre setting with 90% stating they spent at least half or more of their time there, 80% stated less than quarter of their time in clinic and even less time spent involved with ward based activity. The type of surgery SCP's were involved with most being Urology Oncology Open/Laparoscopic 80% and Robotic 80%. In comparison, Benign or Core urology surgery accounts for only 30%. None theatre activity was found to consist of assessment of new patients 40%, follow ups 60% and investigations 40%. Conclusion: The SCP has become a recognized role in the theatre setting, assisting with and in some circumstances, under indirect supervision, carrying out surgical procedures. What this small survey has highlighted is the other facets to the role, demonstrating their input in Outpatient clinic assessment, follow up reviews and in some cases conducting investigations (Flexible Cystoscope and Urodynamic) on urology patients.